Vliv neschváleného ochranného rámu na vozidle na zranění motocyklisty při dopravní nehodě - Bradáč, Albert; Ďatko, Miroslav; Semela, Marek (Akademické nakladatelství CERM, 2020)
Článek pojednává o řešení reálné dopravní nehody motocyklu s vozidlem, vybaveným neschváleným ochranným předním rámem. Nehodě je posuzována jak z hlediska technického, tak i soudně lékařského a v závěru je shrnuto i právní řešení, ke kterému příslušné orgány dospěly. Tento článek byl již publikován na konferenci ExFoS 2019.

The article deals with the solution of a real traffic accident of a motorcycle with a vehicle equipped with a non-approved protective front frame. The accident is presented from a technical and forensic medicine point of view and also summarizes the legal solution. This article was published at the ExFoS 2019 congress.
Influence of the Non-Approved Protective Frame on the Vehicle to Motorcyclists Injuries During a Traffic Accident
Keywords: dopravní nehoda; motocykl; motocyklista; ochranný rám; zranění; traffic accident; motorcycle; motorcyclist; protective frame; injury